2023
DOI: 10.1038/s41586-022-05653-6
|View full text |Cite
|
Sign up to set email alerts
|

Sub-continental-scale carbon stocks of individual trees in African drylands

Abstract: The distribution of dryland trees and their density, cover, size, mass and carbon content are not well known at sub-continental to continental scales1–14. This information is important for ecological protection, carbon accounting, climate mitigation and restoration efforts of dryland ecosystems15–18. We assessed more than 9.9 billion trees derived from more than 300,000 satellite images, covering semi-arid sub-Saharan Africa north of the Equator. We attributed wood, foliage and root carbon to every tree in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…A comparison of field data confirmed that conventional models could underestimate the AGB of the plots in tropical large trees by approximately 18%. Our results concerning the underestimates agree with those of a recent study using the predictor of the crown area (Tucker et al, 2023) for African dryland forests and isolated trees outside forests.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A comparison of field data confirmed that conventional models could underestimate the AGB of the plots in tropical large trees by approximately 18%. Our results concerning the underestimates agree with those of a recent study using the predictor of the crown area (Tucker et al, 2023) for African dryland forests and isolated trees outside forests.…”
Section: Discussionsupporting
confidence: 90%
“…Currently, the application of new technologies such as laser scanning and artificial intelligence is fundamentally improving the observational capabilities for large tree sizes (Brandt et al, 2020;Calders et al, 2022;Jucker et al, 2017;Yang et al, 2022). A recent study using a predictor of the crown area indicated the great necessity of determining the effects of crowns on allometric scaling (Tucker et al, 2023). Therefore, addressing the…”
Section: Introductionmentioning
confidence: 99%
“…Images were obtained by NASA through the NextView License from the National Geospatial Intelligence Agency. More information on the data source, such as image dates, can be found in 29,32 .…”
Section: Methodsmentioning
confidence: 99%
“…However, such maps do not distinguish between an invasive shrub or a baobab, and merge every woody plant under the variable tree cover. Such tree cover maps are often used to proxy ecosystem services in a given area 30 , although they are better suited to assess carbon stocks, climate change mitigation and wood products 31,32 . The creation of maps that include information on speci c tree species and their distribution represent a promising avenue for improving assessments of the ecosystem services provided by various trees as well as their contributions to local livelihoods 33 .…”
mentioning
confidence: 99%
See 1 more Smart Citation